2012
DOI: 10.1590/s0102-695x2012005000053
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of Lecythis pisonis and cytotoxic activity

Abstract: Abstract:The phytochemical investigation of the ethanol extract from leaves of Lecythis pisonis Cambess., Lecythidaceae, resulted in the isolation of seven triterpenes: α-and β-amyrin, uvaol and erythrodiol, ursolic and oleanolic acids and 3β-friedelinol (friedelan-3β-ol), as well as a mixture of sitosterol and stigmasterol steroids and a diterpene (E)-phytol. The structures of these compounds were identified by 1 H and 13 C NMR spectral analysis and compared with literature data. The mixture of triterpenes ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
5
0
5
Order By: Relevance
“…Bertholletia excelsa e Eschweilera ovata Mart. ex Miers, que são do tipo criptocotiledonar (Santos et al, 2006;Oliveira et al, 2012), o que evidencia uma variação quanto aos tipos de germinação apresentados nesta família.…”
Section: Aspectos Morfológicos Da Germinação E Da Plântulaunclassified
See 1 more Smart Citation
“…Bertholletia excelsa e Eschweilera ovata Mart. ex Miers, que são do tipo criptocotiledonar (Santos et al, 2006;Oliveira et al, 2012), o que evidencia uma variação quanto aos tipos de germinação apresentados nesta família.…”
Section: Aspectos Morfológicos Da Germinação E Da Plântulaunclassified
“…e a embiriba (Eschweilera ovata Mart. ex Miers) (Camargo et al, 2000;Braga et al, 2007, Margatto & Royer, 2009Oliveira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Its nuts are an important source of calories (average: 736.87 kcal/100 g), are rich in calcium, phosphorus, and manganese, and can be consumed by humans and animals as a source of lipids and proteins (Souza et al, 2008). Several parts of the plant have been used in popular medicine, and recent studies have revealed the presence of compounds that have moderate cytotoxic activity (Silva et al, 2012). This plant is used in the wood industry, in the production of cosmetics, for ornamental cultivation, and in the production of handmade objects (Revilla, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the infusion prepared from the bark of the tree is astringent and used in the treatment of diarrhea, while the leaves are used as diuretic and tonicardiac in tea or infusion or in baths to relieve itching (pruritus) and the fruits are used in the treatment of diarrhea and syphilis (Braga et al 2007;Denadai, 2006). The phytochemical study of the leaves of this species led to the isolation of pentacyclic triterpenoids, phytol, sitosterol and stigmasterol (Oliveira et al, 2012). The ethanol extract and the mixture of ursolic and oleanolic acids obtained from the leaves demonstrated antipruritic and cytotoxic activities (Silva et al, 2012;Oliveira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical study of the leaves of this species led to the isolation of pentacyclic triterpenoids, phytol, sitosterol and stigmasterol (Oliveira et al, 2012). The ethanol extract and the mixture of ursolic and oleanolic acids obtained from the leaves demonstrated antipruritic and cytotoxic activities (Silva et al, 2012;Oliveira et al, 2012). Other studies also showed that ethanol extract, eterea fraction and mixture of ursolic and oleanolic acids from leaves of L. pisonis exhibited antinociceptive activity in models of acute pain in mice (Brandão et al, 2013).…”
Section: Introductionmentioning
confidence: 99%